The relationship between traditional performance measures countermovement jump testing in youth female soccer athletes - Momin, S.; Goble, H.; Miller, R.; Liberman, S.; Lambert, B. (International Journal of Exercise Science Conference Proceedings, 2025)
Jump testing using electronic force plates has gained interest in sport and rehabilitation settings for evaluating performance and recovery across all levels, from youth to professional. While these devices produce extensive data on jump metrics, little information exists on how they relate to traditional sport performance measures used in athletic or therapy settings for youth athletes.